Co-Ti-O complex oxides: Hydrothermal synthesis, phase characterization, color analysis and catalytic activity assessment - Apinpus Rujiwatra (2018)
© 2015, Chiang Mai University. All rights reserved. The hydrothermal synthesis of Co-Ti-O complex oxide nanoparticles from the reaction between TiO 2 and Co(NO 3 ) 2 .6H 2 O using the stoichiometric ratio to yield Co 2 TiO 4 and NaOH as mineralizer have been investigated. The particles were characterized by powder X-ray diffraction, selected area electron diffraction, scanning electron and transmission electron microscopies, UV-Vis, infrared and Raman spectroscopies, X-ray absorption near-edge spectroscopy, thermogravimetric analysis and gas sorption measurements. Evidences on the pathogenic formation of Co 3 O 4 and CoTiO 3 are illustrated, and the unlikely in yielding a single phase of Co 2 TiO 4 is revealed. Detailed phase characterization is discussed. The particles showed a dark bluish green color, two different morphologies of rhombus and needle shape with a mean particle size of 150 nm, a remarkably narrow pore size distribution below 75 Å, and type II gas sorption behavior. An excellent performance as a catalyst toward the Fischer-Tropsch synthesis with 35% of CO conversion and a high selectivity toward the C 10 , has been revealed.